Perancangan User Experience Aplikasi Pembelajaran Investasi Pasar Modal berbasis Mobile menggunakan Metode Design Thinking - Widi Aditama; Herman Tolle; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Based on a data from Financial Service Authority (OJK), Indonesian financial literacy in stock market sector is 4,92%, which make it the lowest out of the other financial service sector that exist, based on those data there's need an effort to improve financial literacy in stock market area, a user experience to make mobile application that help users learn how to invest and practicing their investing skills on stock market. The method used in this study is the design thinking method, which consist of gathering information by conducting interviews and handing out questionnaires to finds out the problem and how respondent deals with those problems, analyzing needs to point out the main problem and prioritize user needs, ideate to find solution for the problem, creating mockup from idea to iterate, creating prototype to finalize solution, and testing the product using usability testing that test effectiveness, efficiency, and satisfaction aspect of the solution, two methods used include task scenario to test effectiveness and efficiency aspect, System Usability Scale to test satisfaction aspect. The design got a result of 93,47% for effectiveness, 87,63% for efficiency, and 71,25% for satisfaction and satisfaction score included in group B (Good). The solution obtained final result of 84,41%.